Correction: A Randomized Controlled Trial to Examine the Relationship Between Peer Mentoring for Physical Activity and Cardiometabolic Health - Moradeke Bamgboye; David Adeyemi; Emmanuel Agaba; Susan Yilme; Clement A. Adebamowo; Sally N. Adebamowo (Ubiquity Press, 2024)
This article details a correction to: Bamgboye M, Adeyemi D, Agaba E, Yilme S, Adebamowo CA, Adebamowo, SN. A Randomized Controlled Trial to Examine the Relationship Between Peer Mentoring for Physical Activity and Cardiometabolic Health. Global Heart. 2023; 18(1): 53. DOI: https://doi.org/10.5334/gh.1268.